EFFORTS TO INCREASING WORKER’S KNOWLEDGE ABOUT OBESITY IN THE MANUFACTURING SECTOR - Ratih Damayanti; Indah Lutfiya; Ratnaningtyas Wahyu Kusuma Wardani (Universitas Airlangga, 2023)
Obesity is a health problem that can be experienced by workers in various sectors, especially in the manufacturing sector. The aims of this activity is to improve workers' knowledge level about obesity in manufacturing workers at PT XYZ. The method of this activity is a lecture and question & answer session which are evaluated using pre and post test questionnaires to determine the enhancement in workers' knowledge before and after counseling. Activities are divided into 3 stages, namely preparation, implementation and evaluation. This community service activity went well and effectively because there was a significant increase in knowledge before and after counseling (p-value = 0,000). The company was recommended to make a weight loss program after this community service activity, namely in the form of regular exercise with the workers.